The myth of Narcissus: Metamorphoses of medieval commentary - I. K. Staf (Шаги)
This article traces two types of commentaries on the myth of Narcissus (Ovid, The Metamorphoses, III), which existed in the Middle Ages in French literature in the vernacular — the courtly and the moral and allegorical. The first type of commentary is represented by individual works in which this myth is mentioned (“The Lay of Narcissus”, “The Romance of the Rose”, “The Book of Love Chess” by Evrart de Conty). In these, Ovid’s personage is treated as a violator of Amor’s laws; consequently, he takes on the traits of the “Belle Dame sans merci”. Commentaries of the second kind, such as the poetic and prose versions of “Moralized Ovid” (Ovide moralisé), interpret the figure of Narcissus as the embodiment of the Christian sin of pride, and of Echo as the good name disregarded by the proud man. This second type of commentary fragments the text of the “Metamorphoses” into separate stories and personages, each with its own allegorical meaning. The figure of Narcissus and the story of his death becomes a didactic exemplum that can be used in a sermon. In addition, by the early 15th century, such commentaries had been adopted into treatises on poetry (seconde rhétorique) and poetics (poetria, poetic fiction). In them, Narcissus becomes a rhetorical figure destined to create poetic works of high style. The logical conclusion of this process of fragmentation, which is also embodied in the miniatures of illuminated manuscripts, is the appearance in the 16th century of a new form which Ovid’s poem takes, the form of a collection of emblems.